PENGARUH KONSENTRASI TAPIOKA TERHADAP SIFAT FISIK BIODEGRADABLE FILM DARI BAHAN KOMPOSIT SELULOSA NANAS - Diana Fransisca; Zulferiyenni -; Susilawati - (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2013)
This research was aimed to find the right concentration of tapioca to produce biodegradable films from composite materials of pineapple cellulose with the best physical characteristic. The research was designed using a Completely Randomized Block Design with starch concentration as the single factor. It was consisted of five levels 1%, 2%, 3%, 4% and 5% (w/v) with 5 replications. The data of visual observation and water vapor permeability were analyzed descriptively, while data of tensile strength were processed by analysis of variance. Data homogenity and additivity were tested using Barlett and Tuckey tests. The data were analyzed further by LSD test at 5% level of significance. The best result was the biodegradable film from composite material of pineapple cellulose with 4% tapioca which produced 5228, 59 Mpa for tensile strength and 9.11 g/(m2/hr) for the water vapor permeability. The addition of tapioca in producing biodegradable film from composite material of pineapple cellulose could eliminate floc or the heterogen clump-forming film materials. Keywords: Biodegradable film, tapioca, tensile strength.